Short Notes on the Leaf Architecture and Morphometry of Syzygium spp. Leaves from the Living Collections of Bogor Botanic Gardens - Zahro, Shofiyyatuz; Wahidah, Baiq Farhatul; Hariri, Muhammad Rifqi (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
Studies of leaf architecture and morphometry in Syzygium spp. are investigated. Seven species of Syzygium are taken for the study with additional Psidium guineense Sw. used as comparison. The seven species include Syzygium urceolatum subsp. palembanicum (Miq.) P.S.Ashton, Syzygium tinombalum Sunarti, Syzygium sexangulatum (Miq.) Amshoff, Syzygium hirtum (Korth.) Merr. & L.M. Perry, Syzygium boerlagei (Merr.) Govaerts, Syzygium racemosum (Blume) DC., and Syzygium claviflorum (Roxb.) Wall ex Steud. A comprehensive description of leaf architecture for the studied taxa was provided including leaf type, laminar shape, leaf attachment, laminar length, laminar width, petiole, leaf margin, apex shape, base shape, leaf color, and laminar symmetry. The pattern showed primary vein framework, major secondary spacing, major secondary angle, major secondary vein framework, and tertiary veins. Taxonomically significant leaf features of examined taxa showed great diversity in leaf attachment opposite, primary vein framework pinnate, and major secondary angle smoothly decreasing towards base.ABSTRAK: Kajian arsitektur daun dan morfometri Syzygium spp. diamati dan dilaporkan. Tujuh spesies Syzygium digunakan dan satu spesies Psidium guineense Sw. sebagai pembanding. Jenis Syzygium yang diamati terdiri dari Syzygium urceolatum subsp. palembanicum (Miq.) P.S.Ashton, Syzygium tinombalum Sunarti, Syzygium sexangulatum (Miq.) Amshoff, Syzygium hirtum (Korth.) Merr. & L.M. Perry, Syzygium boerlagei (Merr. Govaerts), Syzygium racemosum (Bl) DC., dan Syzygium claviflorum (Roxb.) Wall ex Steud. Deskripsi arsitektur daun yang diamati mencakup ciri tipe daun, bentuk helaian, letak daun, panjang helaian daun, lebar helaian daun, tangkai daun, tepi daun, ujung daun, pangkal daun, warna permukaan daun, dan simetri helaian daun. Pola venasi menunjukkan primary vein framework, major secondary spacing, major secondary angle, major secondary vein framework, dan tertiary veins. Ciri dengan nilai signifikan ditemukan pada letak daun berhadapan, primary vein framework menyirip, dan sudut sekunder utama yang secara halus berkurang menuju dasar.